Effect of Y2O3 addition on the phase composition and crystal growth behavior of YSZ nanocrystals prepared via coprecipitation process. Issue 9 (November 2015) - Zhou, Yongjiang; Yuan, Wuhua; Huang, Qiaoling; Huang, Wenzhi; Cheng, Haifeng; Liu, Haitao
Abstract: The yttria-stabilized zirconia (YSZ) nanocrystallites were prepared at low temperature using ZrOCl2 ·8H2 O and Y(NO3 )3 ·6H2 O as starting materials by a coprecipitation process. The effects of Y2 O3 addition on the phase transition and crystal growth have been investigated by X-ray diffraction (XRD), Raman spectroscopy, transmission electron microscopy (TEM) and selected area electron diffraction (SAED). The results indicate that the stable tetragonal phase can be obtained at higher temperatures during the heat-treatment process with the increase of Y2 O3 content. Meanwhile, the crystallite size increases with the temperature increasing and the crystal growth rate in the low temperature zone (<800 °C) are obviously smaller than that in the high temperature zone (>800 °C). Owing to different growth mechanisms, the activation energy for crystal growth at low heat-treatment temperatures is much lower than that at higher temperatures.